2018
DOI: 10.3389/fncel.2018.00099
|View full text |Cite
|
Sign up to set email alerts
|

PP242 Counteracts Glioblastoma Cell Proliferation, Migration, Invasiveness and Stemness Properties by Inhibiting mTORC2/AKT

Abstract: Glioblastoma multiforme (GBM) is the most malignant brain tumor and is associated with poor prognosis due to its thorny localization, lack of efficacious therapies and complex biology. Among the numerous pathways driving GBM biology studied so far, PTEN/phosphatidylinositol-4,5-bisphosphate 3-kinase (PI3K)/AKT/mechanistic target of rapamycin (mTOR) signaling plays a pivotal role, as it controls cell survival, proliferation and metabolism and is involved in stem cell maintenance. In front of recent and numerous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 55 publications
1
31
1
Order By: Relevance
“…5). This is in line with previous research showing that upregulation of αKG-dependent Gln metabolism and increased GLS expression promotes the maintenance of cancer stem cells through various mechanisms 26,[62][63][64][65] . Furthermore, Gln metabolism promotes the maintenance of stemness through elevating the synthesis of GSH and maintenance of a balanced redox homeostasis 23,66,67 .…”
Section: Discussionsupporting
confidence: 93%
“…5). This is in line with previous research showing that upregulation of αKG-dependent Gln metabolism and increased GLS expression promotes the maintenance of cancer stem cells through various mechanisms 26,[62][63][64][65] . Furthermore, Gln metabolism promotes the maintenance of stemness through elevating the synthesis of GSH and maintenance of a balanced redox homeostasis 23,66,67 .…”
Section: Discussionsupporting
confidence: 93%
“…Invasiveness is considered as a major determinant for malignant behavior in human gliomas and U251 cells represent a highly invasive tumor [ 38 ]. For this reason, the involvement of UiO-66_N in influencing migration properties was investigated.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, GDC-0941, a highly specific PI3K inhibitor, when combined with TMZ and ionizing radiation (IR), enhances the autophagy response and proapoptotic effects, leading to suppressed cell viability in GB cell lines ( 9 ). Mecca et al reported that PP242 represses GB cell proliferation through induction of high autophagy levels and reduction of cell migration and invasiveness ( 71 ). Choi et al found that treatment with a dual inhibitor of PI3K/mTOR PI-103 increased the cytotoxic and sensitive effects of radiation therapy plus TMZ in GB cells.…”
Section: The Role Of Autophagy In Glioblastoma Therapy With the Phospmentioning
confidence: 99%